2021
DOI: 10.12973/eu-jer.11.1.107
|View full text |Cite
|
Sign up to set email alerts
|

Fostering Students’ Retention in Photosynthesis Using Concept Mapping and Cooperative Mastery Learning Instructional Strategies

Abstract: <p style="text-align: justify;">The performance in biology at the secondary level has not been as good as expected. This has been a matter of concern. Thus, there has been a continuous focus on exploring newer innovative learner-centered and friendly instructional strategies to enhance understanding and retention in biology. This study, therefore, determined the effects of Concept Mapping (CM) and Cooperative Mastery Learning (CML) on fostering retention in photosynthesis among secondary schools in Nyama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 42 publications
1
5
1
Order By: Relevance
“…This means that the use of graphic organizer-enhanced learning strategy is gender sensitive with respect to academic achievement in physics of male and female students. The finding agrees with Bizinmana, et al (2020) that there was gender difference in the mean achievement scores of the students exposed to the cooperative mastery learning with higher achievement gain among the female students.…”
Section: Discussion Of Findingssupporting
confidence: 90%
See 1 more Smart Citation
“…This means that the use of graphic organizer-enhanced learning strategy is gender sensitive with respect to academic achievement in physics of male and female students. The finding agrees with Bizinmana, et al (2020) that there was gender difference in the mean achievement scores of the students exposed to the cooperative mastery learning with higher achievement gain among the female students.…”
Section: Discussion Of Findingssupporting
confidence: 90%
“…The finding agrees with Ivana, (2017) that there was significant difference between girls and boys mean score achievement in physics in favour of boys. However, the finding disagrees with Bizinmana, et al (2020) that male and female students taught using concept mapping showed equal gain in achievement in photosynthesis. The finding also disagrees with Mahmud and Nur (2015) that there was no significant difference in the mean scores of the male and female students' achievement.…”
Section: Discussion Of Findingscontrasting
confidence: 59%
“…Contrary to the control group, the teacher's demonstration and teacher talk prevailed in the lesson. This does not promote a positive attitude towards biology, as witnessed by the overall scores of 44% in the control group and 56% in the experimental group (Bizimana et al, 2022).…”
Section: Discussionmentioning
confidence: 88%
“…Teaching methods play an important role in science to promote learning outcomes, where the attitude of learners helps students to manifest behaviours and interests in a particular subject (Adejimi et al, 2022). Nevertheless, teaching methods dominated by a teacher with teacher's demonstration and chalk and talk have been attributed to the main source of problems that affect students' learning outcomes, including negative attitudes towards science, including biology (Bizimana et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In the second instance, the task to develop educational natural science board games also allowed the preservice teachers to demonstrate knowledge of instructional strategies. Instructional strategies are regarded as specific teaching approaches that are beneficial towards eliciting an effective learning experience in the classroom context (Bizimana et al, 2022.). Examples of instructional strategies in the context of natural science teaching include small-group work activities, cooperative learning activities, class discussion activities, practical hands-on activities, and modelling activities, to name but a few (Botes, 2022).…”
Section: Discussion Of Findingsmentioning
confidence: 99%